Methodology of regulation of new types of weapons by means of international humanitarian law: emergence and development - Melykov, Ruslan (ScienceRise: Juridical Science, 2021)
The purpose of the article is to identify the methodology, used in international humanitarian law for the regulation of new types of weapons. Under the settlement of the objectives of the article, regulation is understood as the establishment of permits, prohibitions and restrictions on the use of this type of weapon in accordance with the basic principles of international humanitarian law. The article is methodologically based on the works of foreign and Ukrainian researchers, devoted to the problems of the settlement of new weapons systems in international humanitarian law. The empirical basis of the article was formed by international treaties in the field of international humanitarian law and codified customs of this industry, as reflected in the codifications, developed by the International Committee of the Red Cross. The article establishes that in international humanitarian law there is an obligation for states to assess the compliance of new weapons systems with international humanitarian law. At the same time, this norm has two disadvantages. First, it is too abstract, which allows states to avoid the obligation to assess each time with reference to the fact that a certain type of weapon does not fall under the definition of a new type of weapon. Secondly, international humanitarian law does not contain specific mechanisms to hold violating states accountable. It is concluded, that it is necessary to revise the current international legal regulation of the obligation to assess new weapons systems in the direction of its concretization and strengthening of responsibility for non-compliance. Corresponding changes can be made to the Additional Protocol to the Geneva Conventions of 1977, or introduced by adopting a separate protocol.